2021
DOI: 10.1007/s10854-020-05131-7
|View full text |Cite
|
Sign up to set email alerts
|

NaInX2 (X = S, Se) layered materials for energy harvesting applications: first-principles insights into optoelectronic and thermoelectric properties

Abstract: In recent times, layered chalcogenide semiconductors have attracted great interest in energy harvesting device applications. In the present study, the structural, electronic, optical and thermoelectric properties of two isostructural chalcogenide materials, NaInS 2 and NaInSe 2 with hexagonal symmetry (R-3m) have been studied using the first principles method. A very good agreement has been found between our results with the available experimental and theoretical ones. The studied materials are semiconducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“… 19 The choice of the pseudopotential is quite important in view of optimization of the crystal structure and its electronic structure, especially of the semiconductor materials. 6 , 20 , 21 The exchange–correlation potentials are evaluated by using the functional form of Perdew–Burke–Ernzerhof (PBE) type within the generalized gradient approximation (GGA) and also of Ceperly and Alder–Perdew and Zunger (CA-PZ) type within the local density approximation (LDA). 18 , 22 , 23 The optimizations for both chalcogenide crystal structures are done by the Broyden–Fletcher–Goldfarb–Shanno (BFGS) method 24 using the following optimization input parameters: a plane wave basis set kinetic energy cutoff of 550 eV, a Monkhorst–Pack k -point mesh size 25 of 6×6×3, an energy convergence threshold of 5 × 10 –6 eV/atom, a maximum force of 0.01 eV/Å, a maximum stress of 0.02 GPa, and a maximum atomic displacement of 5 × 10 –4 Å.…”
Section: Theoretical Methodologiesmentioning
confidence: 99%
“… 19 The choice of the pseudopotential is quite important in view of optimization of the crystal structure and its electronic structure, especially of the semiconductor materials. 6 , 20 , 21 The exchange–correlation potentials are evaluated by using the functional form of Perdew–Burke–Ernzerhof (PBE) type within the generalized gradient approximation (GGA) and also of Ceperly and Alder–Perdew and Zunger (CA-PZ) type within the local density approximation (LDA). 18 , 22 , 23 The optimizations for both chalcogenide crystal structures are done by the Broyden–Fletcher–Goldfarb–Shanno (BFGS) method 24 using the following optimization input parameters: a plane wave basis set kinetic energy cutoff of 550 eV, a Monkhorst–Pack k -point mesh size 25 of 6×6×3, an energy convergence threshold of 5 × 10 –6 eV/atom, a maximum force of 0.01 eV/Å, a maximum stress of 0.02 GPa, and a maximum atomic displacement of 5 × 10 –4 Å.…”
Section: Theoretical Methodologiesmentioning
confidence: 99%
“…CASTEP code allows investigating the electronic properties using local and non-local exchange-correlations functionals. In most cases of semiconducting materials, the functionals of LDA-CAPZ and GGA-PBE underestimate the band gap [20,21]. It is reported that the Heyd-Scuseria-Ernzerhof hybrid functional (HSE06) is one of the approaches that is used to calculate a more accurate band gap of semiconducting materials [22][23][24][25].…”
Section: Electronic Properties Electron Density Difference and Mullik...mentioning
confidence: 99%
“…EDD describes the variations in the electronic charge distribution owing to the formation of all the bonds within the crystal. We have studied the EDD and Mulliken atomic population (MAP) analysis between different atomic elements of these compounds, which are crucially important in order to understand charge transfer, bonding and its nature as well [26,27]. Fig.…”
Section: Electronic Properties Electron Density Difference and Mullik...mentioning
confidence: 99%
See 1 more Smart Citation
“…As this function signifies the energy loss of electrons during the propagation trough the materials, therefore, the zero value of L (ω) up to certain energy indicates no energy loss of electrons. The peak observed at certain energy depicts the character of plasma oscillation and defines the characteristic frequency that is known as the plasma frequency ω p of the material [97]. At ω p , the real part of the dielectric function, ε 1 (ω), becomes positive from below when the ε 2 (ω) < 1.…”
Section: Assessment Of Suitability As Coating Materialsmentioning
confidence: 99%